Mini-review: Molecular Targets of Neuromuscular Blocking Agents on Nicotinic Acetylcholine (ACh) Receptor - Jekmal Malau; Munir Alinu Mulki; Alfina Oktavianti; Isyana S alsabila; Mutia Desvi Putri; Mutiara Alfiyah; Anisa Fauziah; Irene Virda Sakina (Peneliti.net, 2023)
Neuromuscular blocking agents (NMBAs) are the drugs that most frequently involved in IgE-mediated anaphylaxis during anesthesia which can lead to perioperative morbidity and mortality. The nicotinic acetylcholine receptor is an ion channel composed of ligands consisting of 5 protein subunits. Receptors Nicotinic acetylcholine is extensively expressed to include both receptors of heteromeric or homomeric combinations of α2–α10 and β2–β4ubunits and medicines that act as nicotinic acetylcholine receptor blockers. The mesolimbic pathway in the ventral tegmental area (VTA) and nucleus accumbens mediates neuronal excitability and dopamine (DA) neurotransmission through the use of ethanol and nicotinic acid (NAc). Drugs belonging to the nicotinic acetylcholine categories are Sugammadex, Gantacurium, Cyclodextrin, Vecuronium, Pancuronium, Rocuronium, and Edrophonium. Enzyme Cholinesterase is an enzyme that degrades Ach released through the neuromuscular synaptic cleft.